Generics and Alternatives - Kochari, Arnold; Van Rooij, Robert; Schulz, Katrin (Frontiers in Psychology, 2020)
In this paper we argue that for the (probabilistic) interpretation of generic sentences of the form “Gs are f,” three types of alternatives play a role: (i) alternative features of f, (ii) alternative groups, or kinds, of G, and (iii) alternative causal background factors. In the first part of this paper we argue for the relevance of these alternatives. In the second part, we describe the results of some experiments that empirically tested in particular the second use of alternatives.